2008
DOI: 10.1073/pnas.0800417105
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of behavioral and autonomic responses after lesions of the primate orbitofrontal cortex

Abstract: Successful adaptation to changes in an animal's emotional and motivational environment depends on behavioral flexibility accompanied by changes in bodily responses, e.g., autonomic and endocrine, which support the change in behavior. Here, we identify the orbitofrontal cortex (OFC) as pivotal in the flexible regulation and coordination of behavioral and autonomic responses during adaptation. Using an appetitive Pavlovian task, we demonstrate that OFC lesions in the marmoset (i) impair an animal's ability to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 48 publications
6
47
1
Order By: Relevance
“…Specifically, OFC lesions render monkeys less able to suppress arousal when the contingency between a CS+ and reward is abolished. By contrast, lesions of this area spare acquisition and expression of conditioned autonomic arousal (24). It therefore seems unlikely that damaging fibers running to or from the OFC could account for the present pattern of results.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Specifically, OFC lesions render monkeys less able to suppress arousal when the contingency between a CS+ and reward is abolished. By contrast, lesions of this area spare acquisition and expression of conditioned autonomic arousal (24). It therefore seems unlikely that damaging fibers running to or from the OFC could account for the present pattern of results.…”
Section: Discussioncontrasting
confidence: 39%
“…This study sought to identify the previously uncharacterized effects of lesions specifically targeting the subgenual ACC, and is one of only a handful to assess the effects of cortical lesions on autonomic arousal in primates (23)(24)(25)(26). The subgenual ACC is one of the least accessible parts of the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, Reekie et al (115) found an effect of PFo lesions on autonomic responses. On a probe test in which the CS stops and the predicted reward fails to appear, marmosets with PFo lesions maintain an abnormally high level of arousal (Fig.…”
Section: Hyper-emotionality In the Absence Of An Expected Eventmentioning
confidence: 94%
“…Then, on a probe test in which the CS stops and the predicted reward fails to appear, marmosets with PFo lesions maintain an abnormally high level of arousal (Fig. 3b) [16••]. …”
Section: Orbital Prefrontal-amygdala Interactionsmentioning
confidence: 99%
“…On a subsequent probe trial, the tone stopped (CS off) and the predicted food failed to appear (US omission). Points to left show BP during tone presentation; the series of points to the right show BP as a function of time after CS offset on the probe trial [16••]. Error bars: SEM.…”
Section: Figuresmentioning
confidence: 99%